Daily Behavior Turtledove (Streptopelia Chinensis) In The Field Tennis University Of Lampung - Ganda Wisnu Putra; Sugeng Prayitno Harianto; Nuning Nurcahyani (Jurnal Sylva Lestari, 2014)
This research was conducted in the area of green open Lampung University, to determine the daily behavior of doves (Streptopelia chinensis) in the presence of human activity. The experiment was conducted in September- October 2013 at the University of Lampung tennis courts. The experiment was conducted using focal animal sampling methods and methods of direct observation. Time data collection performed in the morning at 6:00 to 08:00 pm and afternoon at 4:00 p.m. to 18:00 pm six repetitions with no conditions and no human activity of human activity. Data were analyzed descriptively to determine why the behavior of doves and turtledoves are still active on the tennis court, while there are many human activities. The results showed that the daily behavior of doves on the tennis court Lampung University include : perch, moving, flying, silent, eating, resting, incubating eggs, feathers browse, and make a nest. Activity that most people do is sit with the frequency and percentage of 36.47 % and a 9.3 times when there is human activity, 7.8 times and 30.11 % when there is no human activity. Activity that is at least eat the frequency and percentage of 0.1 times and 00:39 % when there is human activity, 0.3 times and 1:15 % in the absence of human activity. Doves keep doing the activity on the tennis court for tennis has a good habitat conditions for rest , a place to sleep, breed, and safe from threats and harassment. Keywords: human activity, daily behavior, turtledove (Streptopelia chinensis), University of Lampung